Method for preparing iron carbide catalyst by mechanical ball milling assisted liquid phase carbonization method and method for preparing olefin by using iron carbide catalyst
The preparation of iron carbide catalysts through mechanical ball milling assisted liquid phase carbonization method solves the problem of high cost of fossil energy and precious metal catalysts consumed by the traditional Fischer Tropsch synthesis process, and achieves low-cost, environmentally friendly catalyst preparation and efficient olefin preparation.
Patent Information
- Application Number
- CN202411812855.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The traditional Fischer Tropsch synthesis process consumes a large amount of fossil energy and produces a large amount of carbon dioxide. The cost of precious metal catalysts is high, making it difficult to achieve sustainable development.
The iron carbide catalyst was prepared by mechanical ball mill assisted liquid phase carbonization method, nanoferric as a precursor, and iron carbide (Fe5C2) catalyst was prepared by liquid phase carbonization method, and applied to Fischer Tropsch synthesis to prepare olefins.
A low-cost and environmentally friendly catalyst preparation is achieved. The catalyst can not only efficiently utilize solar energy for photothermal conversion, but also has good selectivity for product olefins.
Smart Images

Figure CN119702031A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing an iron carbide catalyst by a mechanical ball milling assisted liquid phase carbonization method, and in particular to a method for preparing an iron carbide catalyst by a mechanical ball milling assisted liquid phase carbonization method using iron powder as a raw material and a method for preparing olefins using the obtained catalyst. Background Art
[0002] Fischer-Tropsch Synthesis (FTS) is one of the important process routes for directly converting synthesis gas (a mixture of CO and H2) into chemical raw materials such as olefins. As a basic chemical raw material, olefins are widely used in the production of plastics, detergents, cosmetics and other products. Traditional Fischer-Tropsch synthesis is carried out at high temperature (230-450℃) and high pressure (2-5MPa), using fossil fuel combustion or electricity to provide heat. Therefore, it consumes a large amount of fossil energy and produces a large amount of carbon dioxide emissions, exacerbating the greenhouse effect. As a clean and renewable energy source, solar energy is green and pollution-free and has the potential to replace fossil fuels for energy supply. Photothermal catalysis absorbs light energy through catalysts and converts it into heat energy, driving chemical reactions, which can improve the efficiency of solar energy utilization.
[0003] In the process of Fischer-Tropsch synthesis, transition metal-based catalysts (Co, Ni, Fe, Ru) all show catalytic activity. Among them, the noble metal catalyst Ru has high cost, which is not conducive to practical application; Ni-based catalysts have strong hydrogenation ability and are often used in methanation reactions; Co-based catalysts have strong CC coupling ability and are often used to prepare long-chain hydrocarbons; and Fe-based catalysts are widely used in the preparation of olefins by Fischer-Tropsch synthesis due to their low cost, wide sources, and high selectivity for olefins. Among them, χ-Fe5C2 is considered to be the main active component of iron-based Fischer-Tropsch synthesis to prepare olefins.
[0004] The Fischer-Tropsch synthesis reaction is considered to be a structure-sensitive reaction, which means that the catalytic performance is closely related to the particle size of the active components of the Fischer-Tropsch synthesis (generally including metals and metal carbides). Therefore, studying the size effect of metal / metal carbide nanoparticles in the Fischer-Tropsch synthesis is of great significance for the design of Fischer-Tropsch synthesis catalysts. Mechanical ball milling is a simple and feasible method for large-scale synthesis of nanomaterials through continuous friction, extrusion and collision between grinding beads and raw materials, thereby reducing the average particle size of the particles. It is favored by industrial production. The preparation method of iron carbide catalyst assisted by mechanical ball milling using iron powder as raw material requires extremely low energy consumption and is environmentally friendly. Summary of the invention
[0005] The purpose of the present invention is to propose a method for preparing an iron carbide catalyst by a mechanical ball milling-assisted liquid phase carbonization method, and to explore the application prospects of the obtained iron-based catalyst in the preparation of olefins by Fischer-Tropsch synthesis. The present invention is based on the preparation of nano-iron as a precursor by mechanical ball milling, and the iron carbide (Fe5C2) catalyst is prepared by liquid phase carbonization, and the obtained catalyst is applied to the preparation of olefins by Fischer-Tropsch synthesis. The preparation cost of the catalyst is low, the preparation process is environmentally friendly, and the prepared Fe5C2 catalyst can not only efficiently utilize solar energy for photothermal conversion, but also has good selectivity for the product olefins.
[0006] To achieve the above object, the present invention adopts the following technical solutions.
[0007] A method for preparing an iron carbide catalyst using a mechanical ball milling-assisted liquid phase carbonization method comprises the following steps:
[0008] (1) Weigh commercial reduced iron powder and stainless steel beads into a stainless steel ball mill, add a grinding aid (ethylene glycol for example), and then fill the ball mill with inert gas for ball milling. After the ball milling is completed, wash and dry the powder to obtain a nano-iron precursor.
[0009] (2) The carbon source, solvent, induction agent and the precursor obtained in step (1) are fully mixed under stirring, and the temperature is raised to 330-350° C. under an inert atmosphere, and the temperature is kept for 10-60 minutes. After the reaction system is cooled, the solid-liquid separation is carried out, and the collected solid is washed alternately with a non-polar solvent and a polar solvent, and then dried to collect the iron carbide catalyst.
[0010] Furthermore, in step (1), the ratio of ball milling beads, iron powder and grinding aid during wet grinding is 20:1:2. For different materials, the specific ratio needs to be determined through ball milling tests; the inert gas is nitrogen, argon, helium, etc.; the washing method is to use anhydrous ethanol to wash until the solution is clear; the drying method is vacuum freeze drying overnight, and the drying temperature is -50 to -40°C.
[0011] Furthermore, in step (2), the carbon source is octadecylamine; the solvent is octadecylamine; the inducer is hexadecyltrimethylammonium bromide or ammonium bromide; the inert atmosphere is nitrogen, argon or helium; the non-polar solvent can be selected as n-hexane; the polar solvent can be selected as anhydrous ethanol; the washing method is washing with ethanol and hexane alternately until the solution is clear; the drying method is vacuum freeze drying overnight, and the drying temperature is -50 to -40°C.
[0012] Furthermore, in step (2), the obtained iron carbide particles have Fe5C2 as the main active component, and the nanoparticle size is 10-90nm, which can show high catalytic activity and is particularly suitable for catalyzing Fischer-Tropsch synthesis.
[0013] The iron carbide catalyst prepared by the above method can provide energy through thermal energy and can also drive chemical reactions by absorbing sunlight.
[0014] The Fe5C2 catalyst prepared by the above method exhibits good catalytic activity and stability in both intermittent reaction systems and flow reaction systems.
[0015] (1) Using a batch reaction system specifically includes the following steps:
[0016] Placing an iron carbide catalyst in a reaction system and evacuating the reaction system;
[0017] The synthesis gas is introduced into the reaction system, wherein the synthesis gas includes a mixed gas of CO, H2 and inert gas, wherein the volume ratio of CO and H2 is 1:1-1:3, and the rest is inert gas, the reaction pressure is 1-2 bar, the reaction temperature is 300-340°C, a high-temperature heating plate or a full-spectrum xenon lamp is used to provide heat energy, the reaction time is 0.5-2h, and the product is detected by gas chromatography.
[0018] (2) Using the flow reaction system specifically includes the following steps:
[0019] Placing an iron carbide catalyst in a reaction system, and passing synthesis gas into the reaction system until the residual air in the reaction gas is exhausted, wherein the synthesis gas comprises a mixed gas of CO, H2 and an inert gas, wherein the volume ratio of CO to H2 is 1:1-1:3, and the rest is an inert gas;
[0020] A mass flow meter is used to control the synthesis gas to pass through at a certain flow rate, and a high-temperature heating plate or a full-spectrum xenon lamp is used to provide heat. The reaction temperature is 300-340°C, and the reaction is performed every 0.5h. The product is detected by gas chromatography.
[0021] In the intermittent reaction system as described above, the optimal catalyst CO conversion rate can reach 25.0%-84.1%, and the selectivity of olefins is 50.1%-70.2%; in the flow reaction system as described above, the optimal catalyst CO conversion rate can reach 20.0%-76.2%, and the selectivity of olefins is 50.0%-71.8%.
[0022] The present invention has the following beneficial effects:
[0023] 1. The present invention uses nano-iron obtained by mechanical ball milling as a precursor to prepare Fe5C2 catalyst. The preparation process is environmentally friendly and helps promote the green large-scale production of Fe5C2.
[0024] 2. The present invention uses commercial reduced iron powder as the synthetic raw material, replacing the expensive and toxic carbonyl iron. Compared with using carbonyl iron as the raw material, the cost is greatly reduced by 76.8%.
[0025] 3. After optimizing the catalyst preparation conditions, the CO conversion rate can reach 34.1% and the olefin selectivity can reach as high as 61.3%. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The X-ray diffraction spectrum (X-ray Powder Diffractometer, XRD) of the Fe5C2 catalyst obtained in Example 1 of the present invention is shown.
[0027] Figure 2 The HRTEM image of the optimal Fe5C2 catalyst obtained in Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0028] Example 1
[0029] A method for preparing an iron carbide catalyst using a mechanical ball milling-assisted liquid phase carbonization method comprises the following steps:
[0030] (1) Weigh 5 g of commercial reduced iron powder and 100 g of stainless steel beads with a diameter of 2 mm into a 100 mL stainless steel ball mill, add 10 mL of ethylene glycol, and fill the ball mill with inert gas. The total ball milling operation time is 10 h, 12 h, 24 h, 48 h, and 72 h, respectively.
[0031] (2) Collect the precipitate in the solution obtained in step (1), wash it by centrifugation with anhydrous ethanol, and dry it to obtain a black powder Mx-Fe precursor (wherein x represents the total running time of the ball mill, unit: h).
[0032] (3) 0.202 g of the Mx-Fe precursor obtained in step (2) was mixed with 14.5 g of octadecylamine and 0.113 g of hexadecyltrimethylammonium bromide, heated to 330-350°C in an inert gas atmosphere, maintained for 10 min, and naturally cooled to room temperature. The crude product was collected and named Mx-Fe5C2 (where x represents the total operating time of the ball mill, unit: h).
[0033] (4) Washing and drying the crude product obtained in step (3) to obtain the iron carbide particles for preparing olefins by photothermal catalytic Fischer-Tropsch synthesis, the main component of which is Fe5C2.
[0034] The iron carbide catalyst prepared according to the above method is applied to the photothermal catalytic Fischer-Tropsch reaction in an intermittent reaction system, 50 mg of iron carbide catalyst is added to a light-transmitting closed reactor, diluted synthesis gas (CO:H2:N2=20:60:20, volume ratio) is introduced, the full spectrum of sunlight is concentrated, and gas chromatography is used to detect the change of products over time to determine the catalyst activity; wherein the reaction temperature is 340°C and the reaction pressure is 0.18MPa.
[0035] Figure 1 The XRD spectrum of the Fe5C2 catalyst obtained in Example 1 is shown. Figure 2 The TEM spectrum of the Fe5C2 catalyst obtained in Example 1 is shown.
[0036] Depend on Figure 1 It can be seen that under this condition, Fe5C2 catalyst with good crystallinity was successfully prepared, and its (510) and (021) crystal plane characteristic peaks were very obvious. Figure 2 It can be seen that the main active component of the catalyst is Fe5C2, and the nanoparticle size is 10-90nm. After the catalyst is irradiated with full spectrum for 0.5h, the catalytic activity and selectivity are shown in Table 1. The ball milling time and the CO conversion rate of the catalyst have a volcano-shaped trend. When the ball milling time is 12h, the CO conversion rate and olefin selectivity reach the best, with a CO conversion rate of 34.1% and an olefin selectivity of 67.3%.
[0037] Table 1 Performance of Fischer-Tropsch synthesis catalyzed by iron carbide
[0038]
[0039] Example 2
[0040] The optimal catalyst prepared according to the method of Example 1 was applied to the photothermal catalytic Fischer-Tropsch reaction in an intermittent reaction system, 50 mg of Fe5C2 catalyst was added to a light-permeable closed reactor, diluted synthesis gas (CO:H2:N2=20:60:20, volume ratio) was introduced, the full spectrum of outdoor sunlight was focused, the product was detected by gas chromatography, and the catalyst activity was determined; wherein the reaction temperature was 340°C, the reaction pressure was 0.18 MPa, and the reaction time was 0.5 h.
[0041] The optimal catalyst prepared in Example 1 performed well under concentrated solar radiation conditions, with a CO conversion rate of 30.1% and an olefin selectivity of 65.5%, showing a relatively good olefin selectivity.
[0042] Example 3
[0043] The optimal catalyst prepared according to the method of Implementation Case 1 was used to catalyze Fischer-Tropsch synthesis under pure thermal conditions. 50 mg of iron carbide catalyst was added to the reactor, and synthesis gas (CO:H2:N2=20:60:20, volume ratio) was introduced. The reaction temperature was 340°C, and electric heating was used to provide heat for the reaction under pure thermal conditions. The gas pressure was 0.18 MPa, and the product was detected by gas chromatography.
[0044] The optimal catalyst prepared in Example 1 catalyzes Fischer-Tropsch synthesis to produce olefins under pure thermal conditions, with a CO conversion rate of 30.1% and an olefin selectivity of 65.3%.
[0045] Example 4
[0046] The optimal catalyst prepared according to the method of Example 1 was applied to a batch reaction system to catalyze Fischer-Tropsch synthesis under photothermal conditions. 50 mg of iron carbide catalyst was added to the reactor, and synthesis gas (CO:H2:N2=20:60:20, volume ratio) was introduced. The reaction temperature was 340°C and the xenon light intensity was 3.04 W cm -2 , the gas pressure was 0.18MPa, the single reaction time was 0.5h, and the product was detected by gas chromatography.
[0047] The optimal catalyst prepared in Example 1 still maintains good catalytic performance in the intermittent reaction system. Five cycle tests were carried out in the intermittent reaction system. Under photothermal conditions, there was no significant difference in the activity of catalyzing the Fischer-Tropsch synthesis to prepare olefins. The CO conversion rate was maintained at about 30%, and the olefin selectivity was about 65%. There was no obvious deactivation phenomenon, maintaining a high CO conversion rate and olefin selectivity.
[0048] Example 5
[0049] The optimal catalyst prepared according to the method of Example 1 was applied to a flow reaction system to catalyze Fischer-Tropsch synthesis under pure heat conditions. 100 mg of iron carbide catalyst was added to the reactor, and diluted synthesis gas (CO:H2:N2=20:60:20, volume ratio) was introduced until the residual air in the reaction gas was exhausted. The synthesis gas was controlled by a mass flow meter at a certain flow rate (2 mL min -1 ) The catalyst activity is determined by detecting the change of the product over time using gas chromatography. The reaction temperature is 340°C and the reaction pressure is normal pressure (0.1 MPa).
[0050] The optimal catalyst prepared in Example 1 still maintains good catalytic performance in the flow reaction system. Within a reaction time of 6 hours, the CO conversion rate remains at about 46%, and the selectivity of olefins remains at about 65%, with good stability.
[0051] Example 6
[0052] A method for preparing an iron carbide catalyst using a mechanical ball milling-assisted liquid phase carbonization method comprises the following steps:
[0053] (1) Weigh 1 g of commercial reduced iron powder, 1 g of activated carbon, and 100 g of stainless steel beads with a diameter of 2 mm in a 100 mL stainless steel ball mill. Add 10 mL of ethylene glycol and fill the ball mill with inert gas. The total ball milling operation time is 12 h.
[0054] (2) Collect the precipitate in the solution obtained in step (1), wash it by centrifugation with anhydrous ethanol, and dry it to obtain a black powder Fe / C precursor (where x represents the total running time of the ball mill, unit: h).
[0055] (3) 0.202 g of the Fe / C precursor obtained in step (2) was mixed with 14.5 g of octadecylamine and 0.113 g of hexadecyltrimethylammonium bromide, heated to 330-350° C. in an inert gas atmosphere, maintained for 10 min, and cooled naturally to room temperature. The crude product was collected and named Fe5C2 / C.
[0056] (4) Washing and drying the crude product obtained in step (3) to obtain the iron carbide particles for preparing olefins by photothermal catalytic Fischer-Tropsch synthesis, the main component of which is Fe5C2.
[0057] According to the above method, by adding a carrier (such as C, SiO2, Al2O3, etc.) to the ball mill during the mechanical ball milling method, a supported iron carbide catalyst can be synthesized, and the synthesis method is simple and fast. In addition, by changing the feed ratio of the carrier to the commercial reduced iron powder, a catalyst loaded with different proportions of the carrier can also be obtained, which has a very broad application prospect and high practical value, and the method has strong universality.
[0058] In summary, the present invention provides a method for preparing an iron carbide catalyst using a mechanical ball milling-assisted liquid phase carbonization method, which greatly reduces the synthesis cost and makes the catalyst preparation process environmentally friendly. The obtained iron carbide catalyst can be applied to Fischer-Tropsch synthesis to prepare olefins with high selectivity.
[0059] The contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0060] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made on the basis of the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing an iron carbide catalyst by mechanical ball milling assisted liquid phase carbonization, comprising the following steps: (1) Weighing commercial reduced iron powder and stainless steel beads into a stainless steel ball mill, adding ethylene glycol as a grinding aid, and then filling the ball mill with inert gas to perform ball milling. After the ball milling, the powder is washed and dried to obtain a nano iron precursor; (2) The carbon source, solvent, inducer and the precursor obtained in step (1) are fully mixed under stirring, and the temperature is raised to 330-350° C. under an inert atmosphere, and the temperature is kept for 10-60 minutes. After the reaction system is cooled, the solid-liquid separation is carried out, and the collected solids are washed alternately with non-polar solvents and polar solvents, and then dried to collect the iron carbide catalyst.
2. The method for preparing an iron carbide catalyst by mechanical ball milling assisted liquid phase carbonization according to claim 1, characterized in that: In step (1), the ratio of ball milling beads, iron powder and grinding aid during wet grinding is 20:1:2; the inert gas is nitrogen, argon or helium; the washing method is to use anhydrous ethanol to wash until the solution is clear; the drying method is vacuum freeze drying overnight, and the drying temperature is -50 to -40°C.
3. The method for preparing an iron carbide catalyst by mechanical ball milling assisted liquid phase carbonization according to claim 1, characterized in that: In step (2), the carbon source is octadecylamine; the solvent is octadecylamine; the inducer is hexadecyltrimethylammonium bromide or ammonium bromide; the inert atmosphere is nitrogen, argon or helium; the drying method is vacuum freeze drying overnight, and the drying temperature is -50 to -40°C.
4. The method for preparing an iron carbide catalyst by mechanical ball milling assisted liquid phase carbonization according to claim 1, characterized in that: In step (2), the obtained iron carbide particles have Fe5C2 as the main active component, the nanoparticle size is 10-90nm, can show high catalytic activity, and are suitable for catalyzing Fischer-Tropsch synthesis.
5. A method for preparing olefins using an iron carbide catalyst obtained by any one of claims 1 to 4, characterized in that: The iron carbide catalyst drives the chemical reaction by providing heat through external electrical energy or by absorbing sunlight.
6. The method for preparing olefins according to claim 5, characterized in that: The iron carbide catalyst exhibits good catalytic activity and stability in both intermittent reaction systems and flow reaction systems. (1) Using a batch reaction system specifically includes the following steps: Placing an iron carbide catalyst in a reaction system and evacuating the reaction system; The synthesis gas is introduced into the reaction system, wherein the synthesis gas includes a mixed gas of CO, H2 and an inert gas, wherein the volume ratio of CO to H2 is 1:1-1:3, and the rest is an inert gas, the reaction pressure is 0.1-0.2MPa, the reaction temperature is 300-340°C, a heating base or concentrated sunlight is used to provide heat energy, the reaction time is 0.5-2h, and the product is detected by gas chromatography; (2) Using the flow reaction system specifically includes the following steps: Placing an iron carbide catalyst in a reaction system, and passing synthesis gas into the reaction system until the residual air in the reaction gas is exhausted, wherein the synthesis gas comprises a mixed gas of CO, H2 and an inert gas, wherein the volume ratio of CO to H2 is 1:1-1:3, and the rest is an inert gas; A mass flow meter is used to control the synthesis gas to pass through at a certain flow rate. A heating base or concentrated sunlight is used to provide heat. The reaction temperature is 300-340°C. The reaction is performed every 0.5h, and the product is detected by gas chromatography.
7. The method for preparing olefins according to claim 6, characterized in that The catalytic performance for preparing olefins is as follows: in the intermittent reaction system, the CO conversion rate of the catalyst is 25.0%-84.1%, and the selectivity of olefins is 50.1%-70.2%; in the flow reaction system, the CO conversion rate of the optimal catalyst is 20.0%-76.2%, and the selectivity of olefins is 50.0%-71.8%.
Citation Information
Patent Citations
Preparation method of iron-based catalyst separated and purified by magnetic field and method for preparing low-carbon olefin by using iron-based catalyst
CN117943078A